RENCAIA BISNIS USAHA CUCI DAN SALON KEIIDARAAN BERMOTOR''SPLASH ZONE'' - , Ilwan Eko Hartanto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Growth in the number of motor vehicles contributes to the development of cleaning and maintenance for cars and motorcycles business. The number of cars and motorcycles in Yogyakarta continue to increase every year. This makes Yogyakarta a potential region to run the business of wash and salon for motor vehicles. Therefore, a business plan needs to be formulated that will be useful as a guideline in running the business. The formulation of this business plan includes analysis of external and internal environment by using business model canvas approach which is analyzed using nine building blocks. The concept offered in this business plan focuses on the creation of several value propositions for certain consumer segments. Value propositions offered includes accessibility, convenience, and customization. The result proves that this business is feasible to do because the financial analysis shows that the business is able to fulfill financial feasibility. Based on analysis cash flow for 10 years, it finds out that the NPV is Rp 654.818.357,88, the IRR is 19,12%, and the payback period is 5,57 years.